PENGARUH PENGUNGKAPAN ESG (ENVIRONMENTAL, SOCIAL, GOVERNANCE) TERHADAP NILAI PERUSAHAAN DI BEI PERIODE 2021-2023 - Risky Nila Pebrianti; Sekar Mayangsari (STMIK Widuri Jakarta, 2025)
This study investigates the effect of Environmental, Social, and Governance (ESG) disclosures on the firm value, measured using Tobin's Q, for energy sector companies listed on the Indonesian Stock Exchange (IDX) during the 2021-2023 period. Using secondary data sourced from annual and sustainability reports, this study applies a multiple linear regression model to analyze the relationship between ESG disclosures and firm value. The findings reveal that environmental, social, and governance disclosures significantly influence the firm value, with a combined effect of 58.4%. These results suggest that transparency in ESG practices can enhance firm reputation, especially in high-risk industries like energy.